Seleksi Aktinomisetes dalam Menghasilkan Indole Acetic Acid dan Efektivitas Terhadap Perkecambahan Benih Cabai Merah (Capsicum annum L.) - Anggraini, Yeyen Septia; Linda, Tetty Marta; Lestari, Wahyu (Biospecies, 2018)
Indole Acetic Acid (IAA) is an important that could improve plant growth. Actinomycetes is one group of bacteria that could produce IAA. The purpose of this study was to examines the potential of actinomycetes from Siak, Riau Peatland in producing IAA the effects to red pepper (Capsicum annuum L.) germination. The result of this study was collected 21 isolates of actinomycetes which able only to produced IAA in SCB (Starch Casein Broth) medium with tryptophan addition. The produce highest IAA in L225 isolate with concentration 37,70 Â± 1,00 Âµg/ml by medium SCB with typtophan addition. 14 isolates gave respons for length of sprouts parameters and 20 isolates gave effect to the root length parameters for red pepper seeds with incubation for 15 day.